Outcomes of Push and Pull Percutaneous Endoscopic Gastrostomy Placement in Patients - Ehsan Rahim Memon, Prem Kumar, Shaista Zeb, Imran Arshad, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: The placement of a percutaneous endoscopic gastrostomy tube is now the preferred nutritional support device for long-term dysphagia patients. Based on the timing, tube dislodgement could cause significant morbidity. The present study’s goal was to assess the outcomes of push and pull percutaneous endoscopic gastronomy placement in patients. Methodology: A descriptive-analytical study was carried out on 264 patients’ undergone placement in percutaneous endoscopic gastrostomy tubes during the period from November 2018 to October 2021 at the Department of Gastroenterology and Hepatology of Isra University Hospital, Halaroad Hyderabad. Demographic details, indications, underlying diagnosis, and complications of the patients were assessed via medical records. Psychological status, physical and social performance, and health-related life issues were addressed through a pre-designed questionnaire. Results: Of the total 264 patients undergone PEG placement procedure, the prevalence of successful PEG tube placement was 256 (97%). Out of successful PEG tube placement in 256, the incidence of push and pull was 158 (59.8%) and 106 (39.2%) respectively. The overall mean age was 56.8 ± 8.5 years and patients were followed far a year. Tube dislodgement (p<0.001) and Peri-procedural bleeding (p=0.001) were significantly associated with push percutaneous endoscopic gastrostomy tubes placement while infected site (p=0.021), buried bumper (p<0.001), and granulation tissue formation (P = 0.032) were associated with pull PEG. Mortality rate was 0.3% in placement of percutaneous endoscopic gastrostomy tubes. Conclusion: Our study found that placement of push and pull percutaneous endoscopic gastrostomy tubes placement are safe procedures. PEG-tubes placement was establish to be relatively free of serious immediate and long-term complications. The majority of caregivers and patients agreed that PEG-tubes aided in feeding and extending survival.